Pengaruh Model Pembelajaran Inkuiri Bebas yang Dimodifikasi terhadap Keterampilan Proses Sains Siswa pada Konsep Panas dan Perpindahannya - Reza Ruhbani Amarulloh; Fatimah Nurul Alisya (Universitas Garut, 2025)
The purpose of this study was to examine the effect of the Modified Free Inquiry model on improving students' modeling skills on the topic of temperature, heat, and their transfer. The research method used in this study was a quasi-experimental design with a non-equivalent control group. Participants in this study involved two groups of eleventh-grade students at a State Islamic Senior High School in Jakarta, each class consisting of 36 students. The experimental class was given learning using the Modified Free Inquiry learning model while the control group used the Discovery Learning model. The instruments used included a test instrument to measure students' science process skills and an observation sheet used to measure the implementation of learning. The results of the hypothesis test showed a p value = 0.000 (<0.05) which indicated a significant difference between the two classes with the average N-Gain values of the experimental class being 0.90 (high category) and the control class 0.58 (moderate category). The implementation of learning in the experimental class was in the good category (64%), with the problem orientation and problem planning stages reaching the highest percentage (71%). It can be concluded that the use of the Modified Free Inquiry model is effective in improving students' science process skills on the topic of temperature, heat, and their transfer.